2024
DOI: 10.3389/fpsyg.2024.1327272
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-experimental mixed-method pilot study to check the efficacy of the “SOUND” active and passive music-based intervention on mental wellbeing and residual cognition of older people with dementia and dementia professionals’ burnout: a research protocol

Sara Santini,
Alessandra Merizzi,
Ioana Caciula
et al.

Abstract: PurposeThe SOUND method offers an innovative blended intervention based on music circle-activities and cognitive stimulation approaches which was co-designed by musicians, health professionals, older people with dementia, family caregivers and researchers, for its application in dementia settings. The purpose of the paper is to describe the detailed procedure of the quasi-experimental pilot study.MethodThe experimental phase of SOUND uses a mixed-method design encompassing qualitative and quantitative observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…Further studies are needed that show the potentialities disclosed by the use of music in residential and semi-residential care settings. The impact of the SOUND training on OPD’s well-being, mood, behavior, and cognition has already been tested through a quasi-experimental mixed-method research protocol [ 30 ] and the results (that will be reported in another paper) will hopefully contribute to increase the knowledge on the effects of music in the dementia care and shed light on the need of training.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed that show the potentialities disclosed by the use of music in residential and semi-residential care settings. The impact of the SOUND training on OPD’s well-being, mood, behavior, and cognition has already been tested through a quasi-experimental mixed-method research protocol [ 30 ] and the results (that will be reported in another paper) will hopefully contribute to increase the knowledge on the effects of music in the dementia care and shed light on the need of training.…”
Section: Discussionmentioning
confidence: 99%